EMBR-14. RECLASSIFICATION OF CENTRAL NERVOUS SYSTEM PRIMITIVE NEUROECTODERMAL TUMOR (CNS-PNET) INTO ENTITIES REFLECTS OUTCOME: RESULTS FROM THE PROSPECTIVE SJYC07 AND SJMB03 TRIALS. Issue 2 (22nd June 2018) - Liu, Anthony; Orr, Brent; Lin, Tong; Hassall, Tim; Bowers, Daniel C; Bouffet, Eric; Gururangan, Sridharan; Fisher, Paul; Crawford, John; Kellie, Stewart J; Chintagumpala, Murali; Fisher, Michael; et al.
Abstract: BACKGROUND: Central nervous system primitive neuroectodermal tumor (CNS-PNET) was removed from the WHO classification after DNA-methylation profiling unveiled its underlying heterogeneity. Here we describe the makeup and outcome of patients histopathologically diagnosed as CNS-PNET treated on 2 multi-center, prospective trials. METHODS: Patients <3yr received chemotherapy with/without focal irradiation (SJYC07). Patients ≥3yr received risk-adapted craniospinal-irradiation (23.4Gy for localized disease, 36–39.6Gy for metastatic) and chemotherapy (SJMB03). DNA-methylation was performed using Infinium MethylationEPIC BeadChip and profiled on DKFZ molecularneuropathology2.0 classifier. RESULTS: Fifty-six patients were enrolled (SJYC07=32; SJMB03=24) with median age 2.86yr (range: 0.64–19.47). Sixteen were stratified as high-risk including 10 with metastasis. Histopathological diagnosis upon central review was CNS-PNET (n=34), ETMR (n=17), CNS-neuroblastoma/ganglioneuroblastoma (n=3) and HGNET (n=2). 42/56 cases were methylation-profiled into ETMR (N=13), GBM (N=3), MBgroup3 (N=2), CNS-NB-FOXR2 (N=3), CNS-EFT-CIC (N=1), EPN-RELA (N=1), choroid plexus tumor (pediatric B) (N=1), PBgroupB (N=1), normal tissue (N=3), and "no match" (calibrated scores <0.9) (N=14). Median duration of follow-up was 2.24yr (range: 0.06–12.7). 5yr-OS/PFS in SJMB03-AR and -HR patients were 46.7 ± 12.9%/46.7 ± 12.9% and 33.3 ± 15.7%/33.3 ± 15.7% (OS p=0.503; PFS p=0.494). 5yr-OS/PFS in SJYC07-IR and -HR patients were 46.8 ± 10.6%/44.7 ± 10.4% and 57.1 ± 18.7%/14.3 ± 13.2% respectively (OS p=0.973; PFS p=0.046). Patients methylation-profiled as ETMR/GBM/MB had 5yr-OS/PFS of 24.1 ± 10.4%/14.8 ± 8.9% compared to 90.0 ± 9.5%/80.0 ± 12.6% in the other entities (OS p=0.001; PFS p<0.001). Age, metastasis, extent of surgery and treatment protocol did not significantly impact outcome. Classification by DNA-methylation profiling (p=0.037), histopathological diagnosis (p=0.019) and radiation use (p<0.001) were predictive of PFS. CONCLUSION: Outcome of pediatric CNS-PNET varied but better conformed to convention when assigned a new entity.